2019
DOI: 10.1097/rlu.0000000000002761
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Sarcoma on 18F-FDG PET/CT After Treatment of Gorham-Stout Disease of the Maxilla

Abstract: Gorham-Stout disease is a rare disorder characterized by proliferation of lymphatic and vascular channels within bone resulting in osteolysis. A 53-year-old man with Gorham-Stout disease involving the left maxilla underwent previous treatment including radiation therapy and intralesional chemotherapeutic injections. He later presented with anemia, facial pain, weight loss, and nasal cavity hemorrhage. CT imaging demonstrated a mass centered within the right maxillary sinus with locoregional involvement. PET/CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Our patient is young and further disease progression or development of treatment-related toxicity could have devastating consequences. Furthermore, radiation-induced sarcoma after management of skull base GSD has been reported, placing an importance in reducing the total treatment volume 21 . Proton therapy has emerged as another modality to deliver RT for skull base tumors while minimizing integral dose to organs at risk 22,23 .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient is young and further disease progression or development of treatment-related toxicity could have devastating consequences. Furthermore, radiation-induced sarcoma after management of skull base GSD has been reported, placing an importance in reducing the total treatment volume 21 . Proton therapy has emerged as another modality to deliver RT for skull base tumors while minimizing integral dose to organs at risk 22,23 .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Furthermore, radiation-induced sarcoma after management of skull-base GSD has been reported, placing importance on reducing the total treatment volume. 21 Proton therapy has emerged as another modality to deliver RT for skull base tumors while minimizing integral dose to organs at risk. 22 , 23 Therefore, we recommend that conformal RT techniques (IMRT or proton therapy) be considered for the treatment of skull-base GSD refractory to surgical and medical management.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Exclusive involvement of maxilla is rarely described in the literature. Only 4 cases are reported involving the maxilla till date and ours is the 5 th case ( Table 1 ) [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . The remaining 4 cases described in Table 1 showed multicentric involvement of other craniofacial bones.…”
Section: Discussionmentioning
confidence: 99%
“…German Cooperative Group on Radiotherapy for Benign Diseases concluded that radiation therapy can effectively prevent progression of GSD in 80% of case, and advocated dose range of 30 to 45 Gy at 1.8 Gy to 2 Gy per fraction [37]. Of note, radiation could provoke serious side effects, like secondary malignancy and growth restriction in children and adolescents who received high-dose therapy [11, 38].…”
Section: Discussionmentioning
confidence: 99%